Impacts of COVID-19 on people’s food security: Foundations for a more resilient food system - Béné, Christophe; Bakker, Deborah; Rodriguez, Monica Chavarro; Even, Brice; Melo, Jenny; Sonneveld, Anne; McDermott, John; Benin, Samuel; Wiebe, Keith; Place, Frank (CGIAR COVID-19 Hub, 2021)
As part of the work implemented by CGIAR on COVID-19, the COVID-19 Research Hub Working Group 4 “Address food systems’ fragility and build back better” was tasked with implementing a global assessment of the impacts of COVID-19 on food systems and their actors, focusing specifically on the consequences that the pandemic had brought on the food security and nutrition of those who have been affected by the crisis. This includes formal and informal actors of the food supply chains (from producers to street vendors) as well as consumers, in both rural and urban environments. Building on this assessment, the task was then to draw on key principles of resilience in the context of humanitarian and food security crisis, to identify preliminary elements of a food system resilience research agenda.